A spatial and temporal assessment of oceanic eddies in the Eastern Caribbean - Jason D. Tambie (Discover Applied Sciences)
Abstract When coupled with storm surges or high tides, large amplitude eddies significantly affect coastal environments through intensified beach erosion, saltwater intrusion, and flooding. However, little is known about the long-term patterns and characteristics of these eddies in the Eastern Caribbean. A wavelet-based technique was applied to identify and track eddies, while ocean reanalysis data were incorporated for analysis of salinity and temperature characteristics. The study investigated 70 incidents (large amplitude eddies) across three regions of the Eastern Caribbean, using statistics, graphical representations, and spatial visualizations. In Region 1 (Barbados) and Region 2 (southern islands), incidents showed a seasonal trend, primarily occurring from late spring to early summer. The North Brazil Current drives eddy generation and propagation towards Barbados, while incidents near the southern islands are influenced more by local current interactions with shallow bathymetry. Region 3 (northern islands), however showed no seasonal pattern, with eddy incidents largely affected by the North Equatorial Current. Anticyclonic incidents in Regions 1 and 2 showed the lowest mean salinities (33.95 psu; 33.80 psu, respectively), while the highest mean salinity was found in cyclonic eddies in Region 3 (35.22 psu). Significant differences in salinity between eddies and background waters in Region 1, suggest a notable influence from the Amazon Plume. Temperature differences between eddies and surrounding waters were minimal in all regions. Shallow bathymetric features also contribute to eddy growth (area) and movement. This research provides critical quantitative and geospatial information on eddy patterns and characteristics, thereby supporting future coastal and marine ecosystem management in the Eastern Caribbean.